Risk Factors That Associated With Hypertension In Population Of Tlatah Village, Purwosari, Bojonegoro - Ayu Sekar Pawening; Dani Nasirul Haqi (Journal of Public Health Research and Community Health Development, 2021)
Background: Hypertension or also known as high blood pressure is one of the major health problems in society especially in developing countries like Indonesia. As happened in Tlatah Village, Purwosari, Bojonegoro, hypertension case reached 3rd highest cases that reported in reports of village health service visits in 2019 with so many factors cause hypertension where these factors are divided into modified factor and cannot be changed factor. Purpose: This aimed of this study was to determine the risk factors that associated with the incidence of hypertension in Tlatah Village, Purwosari District, Bojonegoro Regency. Methode: This type of research was a descriptive analytic analysis with a cross-sectional study design. The population in this study was the entire population of 557 people and the sample was taken using simple random sampling technique of 83 people. Result: The results of the analysis showed that the variable which was statistically significant and had a significant relationship was the variable of exercise habits with  p-value <0.05 (p = 0.000; OR = 0.528 CI = 0.767-0.239). Conclusin: The conclusion of this study was that exercise habit was a risk factor associated with hypertension incidence in Tlatah Village, Purwosari, Bojonegoro.Keywords : exercise habit, hypertension, hypertension factor